Beispiel Nr: 04
$ \text{Gegeben:} \\ \vec{a}=\left( \begin{array}{c} a_1 \\ a_2 \\ a_3 \\ \end{array} \right)\qquad \vec{b}= \left( \begin{array}{c} b_1 \\ b_2 \\ b_3 \\ \end{array} \right) \qquad \vec{c}= \left( \begin{array}{c} c_1 \\ c_2 \\ c_3 \\ \end{array} \right) \\ \text{Gesucht:} \text{Spatprodukt,lineare Abhängigkeit,Basisvektoren} \\ \\ \textbf{Gegeben:} \\ \vec{a} =\left( \begin{array}{c} 2 \\ 1 \\ 0 \\ \end{array} \right) \qquad \vec{b}= \left( \begin{array}{c} -3 \\ 4 \\ 0 \\ \end{array} \right)\qquad \vec{c}= \left( \begin{array}{c} 1 \\ -5 \\ 2 \\ \end{array} \right) \\ \\ \textbf{Rechnung:} \\ \vec{a}= \left( \begin{array}{c} 2 \\ 1 \\ 0 \\ \end{array} \right) \qquad \vec{b}= \left( \begin{array}{c} -3 \\ 4 \\ 0 \\ \end{array} \right) \qquad \vec{c} = \left( \begin{array}{c} 1 \\ -5 \\ 2 \\ \end{array} \right) \\ V=\left|\begin{array}{ccc} 2\ & -3 & 1\\ 1& 4 & -5\\ 0& 0 & 2 \\ \end{array}\right| \begin{array}{cc} 2\ & -3 \\ 1& 4 \\ 0& 0 \end{array} \\ V=2 \cdot 4 \cdot 2+ \left(-3\right) \cdot \left(-5\right) \cdot 0 + 1 \cdot 1 \cdot 0 \\ - 1 \cdot 4 \cdot 0 - 2 \cdot \left(-5\right) \cdot 0 - \left(-3\right) \cdot 1 \cdot 2 \\ V=22 \\ \text{Die 3 Vektoren sind linear unabhängig - Basisvektoren} $